Pracownicy o elastycznych formach zatrudnienia — analiza językowa wybranych przekazów internetowych - Olejniczak, Elwira (Acta Universitatis Lodziensis. Folia Linguistica, 2012)
This article analyses the linguistic ways of expressing emotions and talking about flexible forms of employment deployed by employees. The Internet is a medium which gives people an opportunity to present what they are really thinking. Flexible forms of employment are very important in today’s world. Many employees are afraid of that concept because they are not guaranteed security at work. They express their objections by using: negative epithets, comparisons, enumerations, parallelisms, examples, rhetorical questions or exclamations typical of colloquial language.